Intra-abdominal aortic balloon occlusion in the management of placenta percreta. Issue 4 (20th February 2022) - Zheng, Weiran; Dou, Ruochong; Yan, Jie; Yang, Xinrui; Zhao, Xianlan; Chen, Dunjin; Ma, Yuyan; Zhang, Weishe; Ding, Yiling; Fan, Ling; Yang, Huixia
Abstract: Background: Massive bleeding is the main concern for the management of placenta percreta (PP). Intra-abdominal aortic balloon occlusion (IABO) is one method for pelvic devascularization, but the efficacy of IABO is uncertain. This study aims to investigate the outcomes of IABO in PP patients. Methods: We retrospectively reviewed the clinical data of PP cases from six tertiary centers in China between January 2011 and December 2015. PP cases with/without the use of IABO were analyzed. Propensity score matching analysis was performed to reduce the effect of selection bias. Postpartum hemorrhage (PPH) and the rate of hysterectomy, as well as neonatal outcomes, were analyzed. Results: One hundred and thirty-two matched pairs of patients were included in the final analysis. Compared with the control group, maternal outcomes, including PPH (68.9% vs . 87.9%, χ 2  = 13.984, P  < 0.001), hysterectomy (8.3% vs . 65.2%, χ 2  = 91.672, P  < 0.001), and repeated surgery (1.5% vs . 12.1%, χ 2  = 11.686, P  = 0.001) were significantly reduced in the IABO group. For neonatal outcomes, Apgar scores at 1 minute (8.67 ± 1.79 vs . 8.53 ± 1.68, t  = −0.638, P  = 0.947) and 5 minutes (9.43 ± 1.55 vs . 9.53 ± 1.26, t  = 0.566, P  = 0.293) were not significantly different between the two groups. Conclusions: IABO can significantly reduce blood loss, hysterectomies, and repeated surgeries. This procedure has not shown harmful effects on neonatal outcomes.